(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to partially and simultaneously influence consumer behavior, product diversity, and store atmosphere on purchasing decisions at the Padma Store in Renon, Denpasar. The population in this study were all consumers of the Padma Store in Renon, Denpasar in 2021 as many as 20,157 people. Determination of the sample using the Slovin formula so that 100 people were obtained as samples taken using the accidental sampling method. Data analysis using multiple linear regression analysis. The results of the analysis show that consumer behavior variables have a positive and significant effect on purchasing decisions, product diversity has a positive and significant effect on purchasing decisions, store atmosphere has a positive and significant effect on purchasing decisions, as well as consumer behavior, product diversity, and store atmosphere simultaneously have positive and significant impacts to purchasing decisions.